How can midlife nurses be supported to deliver bedside care in the acute clinical services until retirement? : a thesis presented in partial fulfilment of the degree of Master of Philosophy (Nursing), Massey University, Turitea, Palmerston North, New Zealand - Dodsworth, Caroline (Massey University, 2008)
As the baby boomer generation move inexorably towards retirement and the requirement for health care services increases, the supply of nurses available to provide care at the patient bedside is forecast to fall significantly short of demand. This thesis has explored the perspectives of midlife nurses, asking what it would take to keep them in bedside practice until retirement. These nurses have provided insights which offer employers of valuable senior nurses, suggestions for maximising their potential. Through the use of questionnaires and focus groups nurses aged 45 years and over were asked what the employer can do to ensure that they are able to continue to work at the patient bedside until they reach the age of retirement. The results of this research demonstrate a workforce of nurses who are passionate and committed to their profession, but feeling disillusioned and disempowered. The nursing environment has changed over the span of their career and they find the increased workload, together with increasing professional demands, too hard to cope with. They feel they have no control over their workload, their shift patterns, or the expectations of their patients and colleagues. They want their experience to be recognized but they do not want to have to prove competency; they want to have a voice but they are unwilling to pursue postgraduate education to learn how to become visible and emancipated.
Keywords: Baby boomers; Professional demands; Age and employment; Nursing practice; Fields of Research::320000 Medical and Health Sciences::321100 Nursing